2019
DOI: 10.3390/robotics8040096
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Age-Related Differences of Ankle Mechanical Properties Using a Robotic Device

Abstract: A deep analysis of ankle mechanical properties is a fundamental step in the design of an exoskeleton, especially if it is to be suitable for both adults and children. This study aims at assessing age-related differences of ankle properties using pediAnklebot. To achieve this aim, we enrolled 16 young adults and 10 children in an experimental protocol that consisted of the evaluation of ankle mechanical impedance and kinematic performance. Ankle impedance was measured by imposing stochastic torque perturbations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(72 reference statements)
1
2
0
Order By: Relevance
“…Even though the ankle mobility is shown as one predictive factor, we can speculate that also kumite athletes should take into account the training focused on the ankle mobility; in fact a poor mobility, i.e., joint rigidity, can lead to a worsening of the performance during jumping, as found in the examined jumping tests and also reported in Reference [54]. Furthermore, it has already been demonstrated as an excessive of ankle rigidity can lead to an increase of injuries [55]. From the same perspective, it would be useful the introduction of specific training sessions addressed to increase the ankle mobility during the training programs of kumite athletes, for example, through BHC (Banded Heel Cord) and BCS (Barbell Calf Smash) programs that allow improving ankle mobility with respect to traditional calf stretch technique [56].…”
Section: Discussionsupporting
confidence: 61%
“…Even though the ankle mobility is shown as one predictive factor, we can speculate that also kumite athletes should take into account the training focused on the ankle mobility; in fact a poor mobility, i.e., joint rigidity, can lead to a worsening of the performance during jumping, as found in the examined jumping tests and also reported in Reference [54]. Furthermore, it has already been demonstrated as an excessive of ankle rigidity can lead to an increase of injuries [55]. From the same perspective, it would be useful the introduction of specific training sessions addressed to increase the ankle mobility during the training programs of kumite athletes, for example, through BHC (Banded Heel Cord) and BCS (Barbell Calf Smash) programs that allow improving ankle mobility with respect to traditional calf stretch technique [56].…”
Section: Discussionsupporting
confidence: 61%
“…Given the importance of ankle stiffness in lower extremity function, it has been extensively studied for the past decades, but most studies have focused on characterizing ankle stiffness in a single plane of movement (Kearney et al, 1990 ; Rouse et al, 2014 ). More recent studies have characterized 2D ankle stiffness in both the sagittal and frontal planes, since it contributes to not only dorsiflexion-plantarflexion (DP) movement in the sagittal plane but also inversion-eversion (IE) movement in the frontal plane (Roy et al, 2009 ; Lee et al, 2011 , 2014b ; Martelli et al, 2019 ). These studies showed that ankle stiffness is highly direction dependent, being significantly higher in DP in the sagittal plane than in IE in the frontal plane.…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach is later developed as referring to a device for postural rehabilitation [20]. In paper [21], Martelli et al propose an analysis of ankle mechanical properties for the design of an exoskeleton to be suitable for both adults and children. Experimental tests have carried out on 16 young adults and 10 children for the evaluation of ankle mechanical impedance and kinematic performance.…”
Section: Advances In Italian Roboticsmentioning
confidence: 99%